Phytochemical Screening, Antioxidant Assay and Cytotoxic Profile for Different Extracts of Chrysopogon zizanioides Roots. Issue 8 (17th June 2021) - Grover, Madhuri; Behl, Tapan; Virmani, Tarun
Abstract: The Chrysopogon zizanioides plant possesses multiple traditional uses, especially in therapeutics, but only a few articles have reported its biological activity. Hence, the present study was planned to explore the phytochemical constituents, cytotoxic potential, radical scavenging activity, and GC/MS (Gas chromatography & Mass spectrometry) analysis of the vetiver root extracts. The roots extracted with different solvents exhibited more significant phytochemical constituents in polar solvents in comparison to non‐polar ones, favoring the extraction of a greater number of components in highly polar solvents. All the extracts were tested for their cytotoxicity using SRB (Sulforhodamine B) assay. They confirmed ethanolic extract as a potent extract with GI50 56±0.5 μg/ml in oral cancer (SCC‐29B) along with no cytotoxicity in healthy cells (Vero cells), making it a safer therapeutic option in comparison to standard Adriamycin. This extract was also analyzed for its antioxidant potential by DPPH (1, 1‐Diphenyl‐2‐picrylhydrazyl) assay with IC50 value 10.73 μg/ml, which was quite comparable to Ascorbic acid having IC50 value 4.61 μg/ml. The quantitative analysis of ethanolic extract exhibited 107 compounds amongst which Khusenic acid, Ascorbic acid, Junipen, gamma‐Himachalene, alpha‐Guaiene were the majorly occurring compounds that can be explored further for their cytotoxic activity. Abstract :